2010
DOI: 10.1007/s10545-010-9131-5
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial medicine: to a new era of gene therapy for mitochondrial DNA mutations

Abstract: Mitochondrial disorders can no longer be ignored in most medical disciplines. Such disorders include specific and widespread organ involvement, with tissue degeneration or tumor formation. Primary or secondary actors, mitochondrial dysfunctions also play a role in the aging process. Despite progresses made in identification of their molecular bases, nearly everything remains to be done as regards therapy. Research dealing with mitochondrial physiology and pathology has >20 years of history around the world. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
6

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 120 publications
0
23
0
6
Order By: Relevance
“…In mammals (e.g. bovine), this complex consists of 45 subunits encoded by separate genes, seven of which are in the mitochondrial genome [1][2][3]. Mutations in these genes lead to diverse pathologies affecting the central nervous system, sensory organs, and skeletal and heart muscle, which may manifest at any stage of life.…”
Section: Introductionmentioning
confidence: 99%
“…In mammals (e.g. bovine), this complex consists of 45 subunits encoded by separate genes, seven of which are in the mitochondrial genome [1][2][3]. Mutations in these genes lead to diverse pathologies affecting the central nervous system, sensory organs, and skeletal and heart muscle, which may manifest at any stage of life.…”
Section: Introductionmentioning
confidence: 99%
“…However, an animal model confirming the pathogenicity of the G11778A mutation has never been developed. Moreover, therapies for disorders caused by mutated mtDNA are inadequate, in large part because of the absence of animal models with mutated mtDNA and with the same genotype and phenotype as the human disorder that would help uncover the pathogenesis of disease and test potential avenues for treatment (11)(12)(13). Current procedures for the introduction of artificially mutagenized mtDNA into mitochondria have generated optic neuropathy in mice with a gene [ND6 G14600A (P25L)] that, when homoplasmic, is responsible for Leigh syndrome in humans (14).…”
mentioning
confidence: 99%
“…The counterpart is that a number of these approaches so far remained confined to one laboratory, and some are openly controversial. Mitochondrial medicine is on the way (e.g., Cwerman-Thibault et al 2011), but the current challenge is to validate independently confirmed and generally accepted biotechnological tools (Lightowlers 2011). The stake is worth the effort.…”
Section: Resultsmentioning
confidence: 99%